2004
DOI: 10.1002/ddr.10352
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo characterization of TC‐1827, a novel brain α4β2 nicotinic receptor agonist with pro‐cognitive activity

Abstract: Nicotine activates specific receptors that are cation-permeable ionic channels located in the central and autonomous nervous systems, as well as at the neuromuscular junction. Administration of nicotine to animals and humans has been shown to enhance cognitive processes. However, side effects linked to the activation of peripheral nicotinic receptors limit the usefulness of nicotine for the treatment of cognitive disorders such as Alzheimer's disease (AD) or mild cognitive impairments (MCI). The synthesis and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 35 publications
(38 reference statements)
0
7
0
Order By: Relevance
“…Since nicotine is a relatively non-selective NNR agonist, we evaluated the effects of the antipsychotics on α4β2/SH-EP1 cells activated by the pro-cognitive α4β2-selective compound TC-1827 (Bohme et al, 2004). We found that TC-1827 dose-dependently activates 86 Rb + efflux from α4β2/SH-EP1 cells, achieving maximal responses at concentrations of 100–300 μM with a potency [EC 50 , mean (95% CI) = 2.1 μM (1.5–3.5)] nearly an order of magnitude less than that of nicotine [18.9 μM (13.1–27.5)] (compare Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since nicotine is a relatively non-selective NNR agonist, we evaluated the effects of the antipsychotics on α4β2/SH-EP1 cells activated by the pro-cognitive α4β2-selective compound TC-1827 (Bohme et al, 2004). We found that TC-1827 dose-dependently activates 86 Rb + efflux from α4β2/SH-EP1 cells, achieving maximal responses at concentrations of 100–300 μM with a potency [EC 50 , mean (95% CI) = 2.1 μM (1.5–3.5)] nearly an order of magnitude less than that of nicotine [18.9 μM (13.1–27.5)] (compare Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To do this we studied the effects of the compounds on receptor function in rat striatal synaptosomes (dopamine release), hippocampal slices (norepinephrine release), oocytes (changes in acetylcholine-evoked currents) and cell cultures (Rb + efflux). To further characterize the interaction of antipsychotics with α4β2 NNRs, the selective α4β2 agonist TC-1827 (Bohme et al, 2004) was used to mimic administration of antipsychotics to smokers with high nicotine plasma levels. The results suggest that non-competitive inhibition of NNRs by atypical antipsychotics may have a clinically significant impact on cognitive function since inhibitory effects occur at concentrations within the range of those achieved in the plasma of human patients.…”
Section: Introductionmentioning
confidence: 99%
“…However, both compounds have been shown to be R4β2* nAChR agonists with negligible activities at ganglionic R3*, R7*, and muscle-type nAChRs. 155,156 Although the agonists displayed binding affinities similar to those of native R4β2* nAChRs, they exhibited markedly different activities in an in vitro assay for striatal DA release, where TC-1734 was a partial agonist with an EC 50 value of 106 nM and where TC-1827 was a full agonist with a 70-fold lower potency. 155,156 Oral administration of both TC-1734 and TC-1827 have been shown to enhance cortical ACh release, and both agonists have improved short-and long-term memory in a battery of rodent models.…”
Section: Sibia/merck Compoundsmentioning
confidence: 99%
“…Mutant mice, missing the gene for the beta2 subunit of nicotinic receptors were not found to benefit from nicotine on the same task (Picciotto et al, 1995 ). Across studies performed in animals, both the alph4beta2 and the alpha7 nicotinic receptors have been found to support performance on memory tests (Bohme et al, 2004 ; Chan et al, 2007 ; Pichat et al, 2007 ).…”
Section: Acetylcholine and Cognitive Functionmentioning
confidence: 99%